PENGEMBANGAN MEDIA PEMBELAJARAN SIKLUS AIR DAN DAMPAKNYA PADA TEMA PERISTIWA DALAM KEHIDUPAN UNTUK KELAS V SDN JETIS II - Candra Kurniawan; Hidayati Hidayati (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to determine the characteristics of the process and product, development of water cycleÂ and to determine the quality criteria for the feasibility of water cycle diorama media on the theme of events in the life of fifth grade SD Negeri Jetis 2. This research is a research and development study with the aim of producing new products. This media uses a 3D development model developed by Thiagarajan, Summel. This study has four stages, namely Define, Design, Develop. The results of this study indicate that the media developed in SD Negeri Jetis 2 in the good category. Based on the assessment of material experts, the good category with a score of 3.84. Based on media experts included in the good category with a score of 3.41. Based on the results of field trials with 8 students, this media was included in the good category, with an average score of 4.03.